2021
DOI: 10.46223/hcmcoujs.soci.en.11.1.1902.2021
|View full text |Cite
|
Sign up to set email alerts
|

The challenges and opportunities of online learning during Covid-19 pandemic

Abstract: As the Covid-19 pandemic continues to spread over a year after the original outbreak, it is critical to have an open mind about the innovations higher education institutions (HEIs) have implemented to keep teaching going, as they may help HEIs if appropriately implemented. The pandemic has caused many activities, including traditional educational activities, to be shut down. This has necessitated a vast wave of response migration for HEIs with Online Learning (OL) as the educational platform. This paper conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…As found by many researchers before, that the students were still found many difficulties in reading English text [14,[22][23][24]. The difficulties of the students improved because the situation of Covid-19 era, because there were many problems faced, such as limited era, limited access or limited motivation\in teaching and also about the internet condition [25][26][27]. Although in boarding school the students studied as usual, however the Covid-19 era also gave effect to their teaching and learning process because not all teachers could come to teach them.…”
Section: Resultsmentioning
confidence: 96%
“…As found by many researchers before, that the students were still found many difficulties in reading English text [14,[22][23][24]. The difficulties of the students improved because the situation of Covid-19 era, because there were many problems faced, such as limited era, limited access or limited motivation\in teaching and also about the internet condition [25][26][27]. Although in boarding school the students studied as usual, however the Covid-19 era also gave effect to their teaching and learning process because not all teachers could come to teach them.…”
Section: Resultsmentioning
confidence: 96%
“…Similarly, in a study by Adnan (2018), students highlighted that e-tutors often failed to provide timely and comprehensive feedback, which hindered their progress. Another study by Quang and Tri (2021) explored the challenges and opportunities of online learning during the Covid-19 pandemic, and findings indicate that communication challenges were a significant issue for both students and teachers. In this regard, communication challenges are a common issue in online learning and several studies have explored this topic (Almaiah, Al-Khasawneh, Althunibat, 2020;Hebebci, Bertiz & Alan, 2020;Khalil et al, 2020).…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…Recently, under the context of Covid-19 emergence, [3] and [8] employed distinctive research methods with different objectives. The former had desk research to review the conveniences and obstacles of virtual learning and found that this kind of teaching was justifiable compared to emergency remote teaching.…”
Section: Challenges and Opportunities Of E-learning Employment At Tertiary Institutionsmentioning
confidence: 99%
“…By contrast, virtual learning hinders teachers and learners from having actual interaction, ineffective interpersonal communication, assessment of students' capabilities, time consumption, and necessary computing literacy. [8] asserted that research and technological innovations are e-Learning's plus point while digital competence, assessment & supervision, heavy workload, and compatibility are the unexpected drawbacks.…”
Section: Introductionmentioning
confidence: 99%